2016
DOI: 10.1007/s00784-016-1863-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of tray-delivered carbamide and hydrogen peroxide for at-home bleaching: a systematic review and meta-analysis

Abstract: Tray-delivered CP gels have a slightly better whitening efficacy than HP-based products in terms of ΔE. This should be interpreted with caution as the data of ΔSGU did not show statistical difference between the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 48 publications
3
70
1
13
Order By: Relevance
“…The bleaching products are mostly based on hydrogen peroxide (HP) or one of its precursors, such as carbamide peroxide (CP) . Recent meta‐analysis has shown that CP is slightly better in terms of whitening effectiveness when compared to HP, demonstrating similar tooth sensitivity and gum irritation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleaching products are mostly based on hydrogen peroxide (HP) or one of its precursors, such as carbamide peroxide (CP) . Recent meta‐analysis has shown that CP is slightly better in terms of whitening effectiveness when compared to HP, demonstrating similar tooth sensitivity and gum irritation …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recent meta-analysis has shown that CP is slightly better in terms of whitening effectiveness when compared to HP, demonstrating similar tooth sensitivity and gum irritation. 8 Temperature is an important factor to be considered for bleaching products, because an increase of 10 C doubles the rate of chemical reaction, accelerating the bleaching treatment. 9 In this regard, the storage of bleaching agents at high temperatures can induce the dissociation of components, reducing the shelf life of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the optical properties of teeth have focused only on the effect of bleaching on tooth color but a few have evaluated the behavior of other optical properties, including fluorescence …”
Section: Introductionmentioning
confidence: 99%
“…9 The peroxides used for tooth whitening not only oxidizes the stain molecule into colorless compounds, it also alters the tooth structure surface which in result reflects the light differently. 10 Most studies on the optical properties of teeth have focused only on the effect of bleaching on tooth color [11][12][13] but a few have evaluated the behavior of other optical properties, including fluorescence. 14,15 Fluorescence is a form of luminescence that consists of the rapid emission of light by fluorophores whose electronic states were excited by absorption of light.…”
mentioning
confidence: 99%
“…2 Revisão de Literatura A odontologia estética vem crescendo a cada dia e se tornando um fator primordial para os pacientes, assim nota-se que os clínicos estão bem conscientes da importância do clareamento dental na prática clínica diária, principalmente por ser uma abordagem segura e conservadora (LUQUE-MARTINEZ et al, 2016).…”
Section: Introductionunclassified